Type of submerged entry nozzle vs. concentration profiles in the intermixed zone of round blooms with a diameter of 525 mm - Michalek, Karel (Materiali in tehnologije, 2012)
This work compares the experimental results of nickel-concentration measurements in the intermixed zone of the continuously cast round blooms witha diameter of 525 mm using two types of submerged entry nozzles (SEN) - a straight-through nozzle and the one with 5-ports. Based on the determination of the system and optical interface in a bloom, a detailed study of the concentration profiles on the bloom surface in a small-radius area, on the right-hand side, and then also on the cross sections of the blooms was carried out. The results were further analysed using the approximation models, and were used to verify the proposed model predicting the intermixed zones for the continuous-casting machines. The developed model was based on the results of the physical and numerical modelling.
Keywords: kontinuirno ulivanje; koncentracijski profili; nikelj; mešanje; šobe; modeli